Eksistensi Dan Kedudukan Hukum Adat Dalam Pergumulan Politik Hukum Nasional - Winardi Winardi (Widya Yuridika, 2020)
The plurality of laws prevailing in Indonesia is the legal need for Indonesian people who are plural. Factually, a customary law  is still required to answer the complexity of the vortex of the global wave. The customary law is values (truth and justice) living among the society.  In developing the substance of the law, the 1945 Constitution explicitly acknowledges and give a place and a basis for the enforceability of the legal norms and legal institutions coming from laws living and being applied in the society, namely customary laws and Islamic laws as parts from the national law. This confirmation deals with the inclusion of two new articles in the second amendment (2000) of the 1945 Constitution namely Article 18 B Verse (2) stating that the state recognizes and respects  units of  customary law communities and their traditional rights as long as they are still alive and  in line with the development of the community and the principle of the Unitary State of the Republic of Indonesia stipulated in the laws. Then, Article 28 verse (3) stating that  cultural identity and traditional community’s rights are respected in accordance with the development of era and civilization.